2019
DOI: 10.1038/s41436-018-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrocytic anemia in Lesch–Nyhan disease and its variants

Abstract: PurposeLesch-Nyhan disease (LND) is an inherited metabolic disorder characterized by overproduction of uric acid and neurobehavioral abnormalities. The purpose of this study is to describe macrocytic erythrocytes as another common aspect of the phenotype.MethodsResults of 257 complete blood counts (CBC) from a total of 65 patients over a 23-year period were collected from two reference centers where many patients are seen regularly.ResultsMacrocytic erythrocytes occurred in 81–92% of subjects with LND or its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…But even in the case that folic acid supplements could not solve the neurological problems, they might be useful to improve some cellular alterations. For instance, patients with LND frequently present macrocytic anemia in adulthood (51,52), and folic acid deficiency induces macrocytic anemia in humans (53). It is possible that the high rate of de novo purine biosynthesis in patients with LND limits the availability of folic acid in the erythroblasts, which in turn would induce ZMP accumulation and ATP depletion to cause macrocytic anemia.…”
Section: (F)mentioning
confidence: 99%
“…But even in the case that folic acid supplements could not solve the neurological problems, they might be useful to improve some cellular alterations. For instance, patients with LND frequently present macrocytic anemia in adulthood (51,52), and folic acid deficiency induces macrocytic anemia in humans (53). It is possible that the high rate of de novo purine biosynthesis in patients with LND limits the availability of folic acid in the erythroblasts, which in turn would induce ZMP accumulation and ATP depletion to cause macrocytic anemia.…”
Section: (F)mentioning
confidence: 99%
“…Tissue differences are most obvious in bone marrow cells and particularly mature erythrocytes, which lack a functional de novo synthetic pathway because of the absence of the first enzyme in the pathway 45 , 46 , 73 . Indeed, the dependence of erythrocytes on HGprt-mediated salvage of hypoxanthine supplied into the circulation by the liver 74 may explain why macrocytic anemia is so common in LND 9 , 45 . Similarly, de novo purine synthesis seems to contribute to cell division and neurogenesis in the developing brain 56 , 75 77 , but the mature brain depends more on purine salvage 55 , 56 , 78 .…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is ubiquitously expressed in all tissues of the body at all stages of development 4 . HGprt deficiency produces pleiotropic clinical effects including overproduction of uric acid leading to kidney stones and gout 5 , brain abnormalities 6 8 , and macrocytic anemia 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, aplastic anaemia which is a serious condition and is clinically problematic. Patients with Lesch–Nyhan syndrome who have HPRT deficiency show anaemic symptoms (Cakmakli et al, ; Hakoda et al, ; Hidalgo‐Laos, Kedar, Williams, & Neiberger, ). Hakoda et al () reported that HPRT is important for early blood cell formation.…”
Section: Discussionmentioning
confidence: 99%